Becoming historians - Banner, James M., Jr., 1935-; Gillis, John R. (University of Chicago Press, 2009)
"In this unique collection, the memoirs of eleven historians provide a fascinating portrait of a formative generation of scholars. Born around the time of World War II, these influential historians came of age just before the upheavals of the 1960s and '70s and helped to transform both their discipline and the broader world of American higher education. The self-inventions they thoughtfully chronicle led, in many cases, to the invention of new fields--including women's and gender history, social history, and public history--that cleared paths in the academy and made the study of the past more capacious and broadly relevant. In these stories--skillfully compiled and introduced by James Banner and John Gillis--aspiring historians will find inspiration and guidance, experienced scholars will see reflections of their own dilemmas and struggles, and all readers will discover a rare account of how today's seasoned historians embarked on their intellectual journeys"--Provided by publisher
Keywords: Historians -- Biography.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Historiography.; Historians; Historiker; Historiker.; Historiker -- biografi.; Electronic books.; Biographies; Biographies.